PERANCANGAN SISTEM PAKAR UNTUK MENDIAGNOSIS PENYAKIT PADA TANAMAN SEMANGKA MENGGUNAKAN METODE FORWARD CHAINING - Gulo, Hubungan; Nopriadi (LPPM Universitas Putera Batam, 2024)
The use of computers began for typing until now computers can become tools that imitate the work of the human brain. The watermelon plant is a fruit plant generally used by Indonesian people. However, watermelon plants are plants that are susceptible to disease attacks. To be able to manage the plants well, farmers need to make efforts to deal with them, both in selecting seeds and increasing production. The source of the problem is the fact that watermelon plants are very susceptible to plant diseases which can and do attack at any time, whether from sprouting or sowing seeds until harvest time. Therefore, this research was carried out by creating an expert system application that provides information about diseases that attack watermelon plants and identifies disease symptoms based on physical characteristics so that the expert system application can help farmers in dealing with diseases and can provide solutions to overcome them. Expert systems are a branch of artificial intelligence that can help humans to solve various problems as if the human were an expert who can solve problems. From this research it can be concluded that the expert system designed can provide accurate diagnoses using the forward chaining.